Ojo Kuwi song As Communist Discourse Formation In the election of the President of the Republic of Indonesia in 2014 - Arhamuddin Ali (IJCAS (International Journal of Creative and Arts Studies), 2015)
The aim of this research is to find answers to song Ojo Kuwi as media of the Republic of Indonesia’s presidential election campaign of 2014. In addition, another purpose is to reveal the campaign messages that are communicated through this song’s lyric. This case study focuses on the study of Ojo Kuwi song along with talk on the Internet news media. Data collected from Internet news, analysis of musical elements and lyrics Ojo Kuwi. As a result of research, discovered an attempt to revive the collective memory of Indonesian communism society. Furthermore, the messages are communicated in Ojo Kuwi lyrics urge people to choose presidential number 1 candidate by providing an explanation of the shortcomings of his opponent.